2000
DOI: 10.1162/089892900562138
|View full text |Cite
|
Sign up to set email alerts
|

Common and Distinct Neural Substrates for Pragmatic, Semantic, and Syntactic Processing of Spoken Sentences: An fMRI Study

Abstract: Extracting meaning from speech requires the use of pragmatic, semantic, and syntactic information. A central question is: Does the processing of these different types of linguistic information have common or distinct neuroanatomical substrates? We addressed this issue using functional magnetic resonance imaging (fMRI) to measure neural activity when subjects listened to spoken normal sentences contrasted with sentences that had either (A) pragmatical, (B) semantic (selection restriction), or (C) syntactic (sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
168
2
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(204 citation statements)
references
References 109 publications
(161 reference statements)
22
168
2
4
Order By: Relevance
“…This finding is in general accordance with recent neuroimaging studies on the processing of spoken words [Binder et al, 2000;Mazoyer et al, 1993] and sentences [Dehaene et al, 1997;Kuperberg et al, 2000;Meyer et al, 2000;Mü ller et al, 1997;Schlosser et al, 1998] that demonstrated activation in anterior and posterior divisions of the STR. In accordance with the predictions, however, the functional activation in the STR varied as a function of intelligibility.…”
Section: Temporal Cortexsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in general accordance with recent neuroimaging studies on the processing of spoken words [Binder et al, 2000;Mazoyer et al, 1993] and sentences [Dehaene et al, 1997;Kuperberg et al, 2000;Meyer et al, 2000;Mü ller et al, 1997;Schlosser et al, 1998] that demonstrated activation in anterior and posterior divisions of the STR. In accordance with the predictions, however, the functional activation in the STR varied as a function of intelligibility.…”
Section: Temporal Cortexsupporting
confidence: 92%
“…Conversely, functional activation in the left and right STR is significantly increased for normal and syntactic speech indicating that grammatical processing during auditory sentence presentation is supported by the STR of both the left and the right hemisphere. This result is in general agreement with recent neuroimaging studies associating auditory sentence comprehension with an involvement of the bilateral STR with the left hemisphere playing a dominant role in right-handed subjects [Kuperberg et al, 2000;Mü ller et al, 1997;Schlosser et al, 1998]. In particular, the (left) anterior STR was shown to play an essential role in processing constituent structures, i.e., general syntactic operations at the sentence-level [Friederici et al, 2000b;Humphries et al, 2001;Meyer et al, 2000;Scott et al, 2000].…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…At least one previous study that directly contrasted narrative-level and sentencelevel comprehension found narrative-specific activation in regions such as ATL, posterior MTG, and DMPFC (Xu et al, 2005). However, other studies have observed greater activation in most of these regions when reading or hearing coherent sentences than random word lists (Bottini et al, 1994;Kuperberg et al, 2000;Stowe et al, 1999;Vandenberghe et al, 2002), suggesting that the difference between narrative-and sentence-level comprehension may be quantitative and not qualitative. Alternatively, narrativespecificity may arise at a hemispheric rather than at a regional level.…”
Section: Introductionmentioning
confidence: 97%